1981
DOI: 10.3109/00365598109179608
|View full text |Cite
|
Sign up to set email alerts
|

Uninhibited Neurogenic Bladder Treated with Prazosin

Abstract: The effect of the new alpha-adrenoreceptor blocking agent prazosin on hypermotility of the urinary bladder was investigated, using controlled cystometry in neurological patients with normal bladder or with uninhibited neurogenic bladder. In short-term administration of prazosin, the bladder capacity was markedly increased and the uninhibited detrusor contraction was diminished. Long-term treatment with prazosin gave subjectively improved micturition in patients with detrusor-sphincter dyssynergia. The cystomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…The mean posterior urethral pres sure fell from 27.7 to 12.4 cm H20 and the mean urethral diameter increased from 3.9 to 10.6 mm. Detrusor pressure was not significantly reduced after alfuzosin (data not shown) as previously reported by others with prazosin (Jensen, 1981a).…”
Section: Resultssupporting
confidence: 89%
“…The mean posterior urethral pres sure fell from 27.7 to 12.4 cm H20 and the mean urethral diameter increased from 3.9 to 10.6 mm. Detrusor pressure was not significantly reduced after alfuzosin (data not shown) as previously reported by others with prazosin (Jensen, 1981a).…”
Section: Resultssupporting
confidence: 89%
“…Prazosin, one of the specific postsynaptic a-adrenoceptor blocking agents, was reported to increase BC markedly and diminish the uninhibited detrusor contraction in neurogenic bladder when administered orally (Jensen 1981). The present study also suggested that prazosin could be available to control detrusor hyperreflexia by intravesical instillation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Prazosin, a selective alpha I adrenergic blocking agent with less side effects, has a documented action on the urethra (Kiruluta et al, 1981), and has been employed by Jensen with good results in four out of five patients with uninhibited bladder (Jensen, 1981).…”
Section: Discussionmentioning
confidence: 99%